Riding waves of innovation and paradigm shifts: the past 20 years of AJET - Huijser, Henk; Deneen, Chris; Corrin, Linda; Han, Feifei (Australasian Journal of Educational Technology, 2025)
This is the fifth in a series of editorials that have reflected on and celebrated the past 40 years of the Australasian Journal of Educational Technology (AJET). In this editorial we look back on the most recent 20 years of AJET and identify some of the key themes in AJET articles during that period. Overall, eight key themes are identified: 1) AI and automation in learning, 2) Assessment and feedback, 3) Equity, inclusion and ethics, 4) Learning analytics and data-informed insight, 5) Pedagogical integration, 6) Professional learning and academic development, 7) Self-regulated learning, and 8) Technology adoption. These themes were identified for the period 2008-2025, where we have used AI to assist in our analysis. The themes for the period 2005-2007 were identified manually through abstracts, titles, introductions, and conclusions. Overall, AJET has for the last 40 years provided a significant forum to discuss educational technologies and resulting innovations. Through it all, what has shone through over the past 40 years is a passion for evidence-based practice that provides the best learning outcomes for learners, initially across the whole education sector, and more recently with a specific focus on tertiary education.